RNA Splicing Factor Mutations That Cause Retinitis Pigmentosa Result in Circadian Dysregulation. Issue 1 (February 2020) - Shakhmantsir, Iryna; Dooley, Scott J.; Kishore, Siddharth; Chen, Dechun; Pierce, Eric; Bennett, Jean; Sehgal, Amita
Circadian clocks regulate multiple physiological processes in the eye, but their requirement for retinal health remains unclear. We previously showed that Drosophila homologs of spliceosome proteins implicated in human retinitis pigmentosa (RP), the most common genetically inherited cause of blindness, have a role in the brain circadian clock. In this study, we report circadian phenotypes in murine models of RP. We found that mice carrying a homozygous H2309P mutation in Pre-mRNA splicing factor 8 ( Prpf8 ) display a lengthened period of the circadian wheel-running activity rhythm. We show also that the daily cycling of circadian gene expression is dampened in the retina of Prpf8- H2309P mice. Surprisingly, molecular rhythms are intact in the eye cup, which includes the retinal pigment epithelium (RPE), even though the RPE is thought to be the primary tissue affected in this form of RP. Downregulation of Prp31, another RNA splicing factor implicated in RP, leads to period lengthening in a human cell culture model. The period of circadian bioluminescence in primary fibroblasts of human RP patients is not significantly altered. Together, these studies link a prominent retinal disorder to circadian deficits, which could contribute to disease pathology.